PROBLEMATIKA MAKKALAWANGENG DALAM MASYARAKAT BUGIS BONE: PERSPEKTIF SOSIOLOGI HUKUM ISLAM - Anna Rahma Syam; Ridhwan; Irma Amalia Ma'ruf; Samsidar; Darliana (FISIP Universitas Malikussaleh, 2026)
This article discusses the problems that arise due to the practice of makkalawangeng in Manurunge Village, Tanete Riattang District, Bone Regency, one of the problems that often occurs among the Bugis community when there are problems in the household that are difficult to resolve and the husband and wife do not want to take the final path of divorce, but the husband and wife only choose to makkalawangeng. The data collection method was carried out using interviews and direct observation. Data analysis through the stages of data reduction, data display, data verification and drawing conclusions. The results of the study show that the practice of makkalawangeng in Bone Regency causes problems such as neglect of rights and obligations between husband and wife, decreased love and affection between husband and wife, the emergence of negative perceptions of children towards parents who no longer live in the same house and the emergence of negative stigma from the surrounding environment. The accumulation of these problems often leads to divorce. The Islamic legal perspective on the problems arising from the practice of makkalawangeng is that it contradicts the principles outlined in Islamic law. Therefore, in the context of the sociology of Islamic law, religious figures as social sectors have a role to provide education about religious values to the community so that they do not engage in makkalawangeng practices so that the goal of marriage is to realize welfare and the household can be sakinah, mawaddah, warahmah.